Military Construction Appropriations for 1965. hearings before the United States House Committee on Appropriations, Subcommittee on Military Construction Appropriations, Eighty-Eighth Congress, second session, on March 18, 24, Apr. 8, 1964. (U.S. Congressional Hearings., 1964)
Considers (88) H.R. 11369.